Nutrient composition of Kansas swine lagoons and hoop barn manure - DeRouchey, Joel M.; Nelssen, Jim L.; Tokach, Michael D.; Murphy, James P.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 236 lagoon and 35 hoop barn manure samples were collected during 2000 from Kansas swine operations to determine the effects of production phase and season of the year on their nutrient concentration. Lagoon analyses revealed that nitrogen concentrations were lower during the summer and fall seasons compared to winter and early spring. In addition, levels of nitrogen were highest in nursery, wean to finish, and finishing lagoons compared with sow and farrow-to-finish lagoons. Phosphorus levels for all lagoons increased from February until June, but then declined steadily throughout the remainder of the year. The concentration of phosphorus also was highest for wean-tofinish and finishing lagoons and the lowest for farrow-to-finish lagoons. No seasonal changes in nitrogen and phosphorus concentrations were observed in manure from hoop barns. Therefore, season and type of production phase affects the nutrient content of Kansas swine lagoons, and producers will benefit from obtaining individual analyses from their lagoons when developing nutrient management plans rather than utilizing published reference values.
Keywords: Swine; Pig; Lagoon; Hoop barn